Impacts of noise pollution on people’s health dwelling in surrounding areas of industrial zones of Gampaha district in Sri Lanka - Ruzaik, Fareena (International Journal of Humanities and Social Science Research, 2020)
Industrial noise pollution in Sri Lanka has become an acute issue with the introduction of open economic policy in 1978. Since then, the changing government’s industrial policy gradually increased the number of industries, targeting export income. Gampaha district was declared as one industrial zone in 2000 and Biyagama free trade zone in the district is prominent among them. The people who live within 100 m distance from industries or industrial zones are more vulnerable to multiple health impacts. 85% of the industries emit noises, which is above the recommended level of 55 dB (A). The existing laws and regulations cannot be strictly implemented, since it is directly linked with the country’s economy and social development. The middle level-contingency approach is the only option to mitigate and manage this issue at a center point. The objective of this study is, to identify and analyze the people’s health impacts, arise from the industrial noise pollution in the Gampaha district. The primary data were collected by measuring the noise level at 04 locations of each of 07 industries, questionnaire survey among the 25 households, and structured questionnaire survey among the industry staff, following the purposive sampling method. The secondary data used for this study were extracted from previous literature. MS-Office was used to analyze the data. The results revealed that the dB(A) levels of the selected industries are above the laid down standard of 55 dB (A) level and the highest noise level of 59.5 dB(A) was emitted from the Steel industry at Jaela. The dwellers are impacted with multiple , health diseases, viz. sleepless (45%), irritation (55%), uncomfortableness (75%), hearing issues (40%), speech issues (75%), and headache (55%). Approximately, 20-30% of respondents have been identified, during the survey; their ordinary way of communication is, speak with a loud sound. Further, 06 industries (85%) accepted that they do not have a noise measuring mechanism, although they are aware of the standards, existing regulations and harmfulness of emitting noise to the environment. This study recommended to re-review and amend the existing regulations, to match with the current requirements and to issue Health Impact Risk Assessment report in parallel to the Environmental Impact Assessment (EIA), prior to grant approval in the future.
Keywords: Noise pollution; health impacts; industries; emissions and vulnerable